2014
DOI: 10.1080/07448481.2014.920337
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Nutrition Education Intervention on Vending Machine Sales on a University Campus

Abstract: The increased purchases of healthier snack options demonstrate encouraging patterns that support more nutritious and healthy alternatives in vending machines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 16 publications
7
35
0
5
Order By: Relevance
“…Preferential pricing strategies that reduce the price of healthier products and increase the price of less healthy products can promote healthier purchases from vending machines . However, this study and a similar audit of an urban Australian university campus found that healthy foods tended to be more expensive.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Preferential pricing strategies that reduce the price of healthier products and increase the price of less healthy products can promote healthier purchases from vending machines . However, this study and a similar audit of an urban Australian university campus found that healthy foods tended to be more expensive.…”
Section: Discussionsupporting
confidence: 86%
“…29 Preferential pricing strategies that reduce the price of healthier products and increase the price of less healthy products can promote healthier purchases from vending machines. 20,[30][31][32] However, this study and a similar audit of an urban Australian university campus 16 found that healthy foods tended to be more expensive. Concern that price and product changes would reduce sales and profit may impede managers from offering healthier food and beverage choices.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The countries of origin of the studies included United States ( n = 10) , New Zealand ( n = 1) and the Netherlands ( n = 1) . Outcome measures included sales data expressed as a proportion of healthier items sold and/or absolute sales number of items ( n = 11) , profits or sales volumes ( n = 7) , nutrient composition of the snacks sold ( n = 2) , acceptability of the intervention to the participants ( n = 1) and dietary changes ( n = 1) . Limitations common to all interventions included a lack of measured changes to diet or weight and inability to determine if measured changes were due to existing clients changing the choices they would normally make or if changes were due to new customers.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles were deemed to have a low risk of bias (26)(27)(28)(29)(30), while the remaining seven articles had a moderate risk of bias (31)(32)(33)(34)(35)(36)(37). For the results of the assessment of the risk of bias, see Table 3.…”
Section: Risk Of Biasmentioning
confidence: 99%